5 Finger Hypnotic Intervention Can Reduce The Stress Of NursesProfessional Students That Will Take The Exam: Intervensi Hipnotis 5 Jari Mampu Menurunkan Stres Mahasiswa ProfesiNers Yang Akan Mengikuti Ujian - Siska Mayang Sari; Dewi Kurnia Putri (Journal of Community Service and Application of Science, 2022)
The average Indonesian Nurse Competency Examination (UKNI) graduation at one of the private universities in Pekanbaru City is still around 80-95%, while UKNI graduation is a graduation requirement for professional student education. Students expressed anxiety in facing UKNI coupled with the experience of many seniors who participated in UKNI more than 2 times (re-takers). The purpose of this community service activity was to overcome the anxiety of professional nurse students in preparation for facing UKNI. This community service activity uses a consultation and counseling approach to the Nurse’s students, totaling 32 people. The intervention carried out was 5-finger hypnosis and psychological consultation with UKNI for 5 working days. Anxiety score assessment using the DASS instrument. The results of this activity obtained a decrease in the anxiety level of nursing profession students by 13.06. This shows that the 5-finger relaxation intervention can be used as an alternative to overcome the anxiety of nursing profession students facing UKNI. It is hoped that nursing education institutions will be able to make a 5-finger hypnosis intervention as a form of consultation to overcome the anxiety of nursing professional students facing UKNI.